Provision of Health Information for Older People by Municipalities in Relation to Aging and Municipal Finances - DONKAI, Saori; SANNAMI, Chihomi; TOSHIMORI, Atsushi; TAKEDA, Masaki (Jouhou media kenkyuu, 2024)
Against the backdrop of the Japanese super-aged society, this study aims to shed light on the provision of health information for older people by municipalities in relation to aging and municipal finances. We examined and analyzed the financial capability indicator and the population aging rate of 316 municipalities in the Kanto region of Japan. Results demonstrated that the information was disaggregated by category—dementia, caregiving, and welfare services, with dementia being the most prevalent. Moreover, we discovered that the greater the financial stability of a municipality and the population aging rate, the greater the availability of the information. However, we also observed that although there were municipalities with a solid financial footing, some provided the information only on a list of welfare services, while others dealt with multiple subjects and actively provided the information, indicating a variety in how the information was provided.